SNAKE AS FUNCTIONAL FOOD BY ARFAK TRIBE COMMUNITY IN MANOKWARI REGENCY PAPUA BARAT - Taran, Denisa Melanesia Kreglika; Sirami, Elieser; Arobaya, Agustina; Sinery, Anton; Sawaki, Saremay Max Romario (MAKILA, 2024)
The Arfak tribe has utilized snakes as functional food for generations. This study aims to describe the pattern of the snake utilization as functional food. This research was conducted using Descriptive Method with semi-structured interview and observation. Data collection was performed in 27 villages in Manokwari Regency. Data analysis was carried out qualitatively and quantitatively. The results showed that the Arfak tribe has utilised five species of snakes as functional food, which are Leiophython albertisii, Apodora papuana, Morelia amethystine, Morelia viridis, and Micropechis ikaheka. The utilised parts are meat, fat and bile. The health benefits of snakes are grouped into four categories, namely curing diseases of the respiratory tract, skin diseases, chronic diseases and increasing body strength and vitality. Although snakes have been utilized and are believed to have health benefits, issues related to zoonosis and the absence of comprehensive studies showing the effectiveness of snakes as medicine have resulted in the utilization of snakes as functional food has been debatable.